As condições crônicas e a incapacidade funcional em idosos - Bento, Carlos Adriano Pla [UNIFESP] (2015)
Objective: to evaluate the prevalence of chronic conditions and examine the relationship between chronic conditions and functional disability in the elderly. Methods: Survey of 759 patients of records evaluated in EPIDOSO project ? Phase 2, from which data of sociodemographic and chronic conditions: self-reported diseases, diagnoses by medical evaluation, impairment, signs, symptoms and surgeries were observed. The association between chronic conditions and disability was analyzed through the logistic regression models. Results: Chronic diseases were observed in 99.5% of patients with mean of 5.7 diseases per individual. The most prevalent diseases were systemic arterial hypertension (70%), dyslipidemia (66%) and arthropathy (59%). Chronic conditions most associated with disability were: gait and balance disorders (OR 8.95 95% CI 5.12 to 15.63), change in muscle strength (OR 3.67 95% CI 1.28 to 11.09 ), urinary incontinence (OR 2.91 95% CI 1,71- 4,93) and falls (OR 2.20 95% CI 1.29 to 3.77). Conclusions: This study showed a high prevalence of chronic conditions after medical evaluation. Highlighting classic chronic diseases with hypertension, joint disease, dyslipidemia and depression, but also organic functional changes such as tooth loss, hearing loss, urinary incontinence; Signs and symptoms, as decreased sexual desire, joint pain and sleep disorders. Chronic conditions not classically characterized as diseases were the most strongly associated with functional disability. The gait and balance changes, change in muscle strength, incontinence and falls were the health problems associated with more disability than the classic diseases such as hypertension and diabetes. The findings of this study show that the maintenance of functional capacity depends not only on control of chronic diseases, but fundamentally the physical, psychological and functional for the elderly.